FRI0376 Dyslipidemia as a newly recognisedfactor associated with damage accrual in early diagnosed sle: results from the multicenter early lupus project inception cohort. (12th June 2018) - Piga, M.; Zanetti, A.; Carrara, G.; Scirè, C.A.; Prevete, I.; Sebastiani, G.D.; Coladonato, L.; Iannone, F.; Bortoluzzi, A.; Govoni, M.; Tani, C.; Mosca, M.; et al.
Abstract : Background: Preventing organ damage is a major challenge in Systemic Lupus Erythematosus (SLE). Objectives: To evaluate factors associated with development of damage in a prospectively followed cohort of early diagnosed SLE patients. Methods: The Early Lupus Project 1 encompasses 9 Italian centres recruiting, from the 1 st January 2012, an inception cohort of consecutive patients diagnosed with SLE within 12 months from appearance of four or more 1997 ACR classification criteria. At study entry and then every 6 months a large panel of data was recorded. Here, we report on factors associated with the development of damage assessed by the SLICC/ACR Damage Index (SDI). Using univariate analysis, we assessed the contribution of covariates collected at baseline (demographic, comorbidities, serological, clinical by BILAG2004 domains, disease activity by ECLAM, HRQoL by visual analogic scale) in the development of damage (SDI from 0 to ≥1). Forward-Backward Cox-regression models were fitted with covariates with p<0.05 to identify factors independently associated with increased risk of damage development. Results: Overall, 279 patients were enrolled in the Early Lupus Project inception cohort up to the 31th of December 2017; 230 patients (89.6% Caucasians, 13.4% males) were eligible for this study having SDI=0 at enrolment and at least 6 months of follow-up. Mean (±SD) age at recognition of 4 ACR criteria was 36.5 (±14.4) years, median disease duration at recruitment was 1.1 months (interquartile range 0.0–4.8) and median follow-up duration was 27.4 months (interquartile range 7.2–48.0). At last follow-up visit 84 patients (36.5%) had an SDI score ≥1 (median=0; interquartile range 0–1); see figure 1A for overall SDI domains involved. Baseline dyslipidemia (p<0.001; HR 2.7 95% CI 1.5–4.8), higher number of BILAG domain involved (p<0.001; HR 1.4 95% CI 1.2–1.7) and older age (>35 year) at baseline (p=0.001; HR 2.3 95% CI 1.4–4.0) together with total dose of corticosteroids (p=0.015; HR 1.06 per gram of prednisone equivalent; 95% CI 1.01–1.11) during follow-up were the factors independently associated with increased risk of developing damage in this cohort (figure 1B). Their effect was confirmed after stratification for antimalarials (yes/no) and immunosuppressants (yes/no) use. Conclusions: The early development of organ damage in this SLE patients cohort was associated with modifiable risk factors as baseline dyslipidemia and higher corticosteroid dose. Addressing them since the very early stages of the disease, and treating disease activity to target remission or minimal disease activity, may reduce damage and improve patients outcome. Reference: [1] Sebastiani GD, et al. Early Lupus Project – A multicentre Italian study on systemic lupus erythematosus of recent onset. Lupus2015Oct;24(12):1276–82. Disclosure of Interest: None declared